2022
DOI: 10.1111/mec.16494
|View full text |Cite
|
Sign up to set email alerts
|

Odorant receptor orthologues in conifer‐feeding beetles display conserved responses to ecologically relevant odours

Abstract: Insects are able to detect a plethora of olfactory cues using a divergent family of odorant receptors (ORs). Despite the divergent nature of this family, related species frequently express several evolutionarily conserved OR orthologues. In the largest order of insects, Coleoptera, it remains unknown whether OR orthologues have conserved or divergent functions in different species. Using HEK293 cells, we addressed this question through functional characterization of two groups of OR orthologues in three specie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 106 publications
1
11
0
Order By: Relevance
“…23 A recent study showed that the olfactory functions of two clades of OR orthologs in three closely related species, Hylobius abietis, Dendroctonus ponderosae, and Ips typographus, are conserved, with ORs in one clade (HabiOR3, DponOR8, and ItypOR6) responding exclusively to 2phenylethanol and those in the other clade (HabiOR4, DponOR9, and ItypOR5) responding to several green leaf volatiles. 24 These results support the hypothesis that the functions of single-copy orthologous OR genes are relatively conserved during evolution and that these genes usually have similar functions and are involved in regulating important insect behaviors. Aphidophagous hoverflies (Diptera: Syrphidae) are a welldocumented beneficial insect group providing dual ecosystem services to agroecosystems.…”
Section: ■ Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…23 A recent study showed that the olfactory functions of two clades of OR orthologs in three closely related species, Hylobius abietis, Dendroctonus ponderosae, and Ips typographus, are conserved, with ORs in one clade (HabiOR3, DponOR8, and ItypOR6) responding exclusively to 2phenylethanol and those in the other clade (HabiOR4, DponOR9, and ItypOR5) responding to several green leaf volatiles. 24 These results support the hypothesis that the functions of single-copy orthologous OR genes are relatively conserved during evolution and that these genes usually have similar functions and are involved in regulating important insect behaviors. Aphidophagous hoverflies (Diptera: Syrphidae) are a welldocumented beneficial insect group providing dual ecosystem services to agroecosystems.…”
Section: ■ Introductionsupporting
confidence: 80%
“…A study found that the OR74a homologues in three Dacini fruit flies, Bactrocera dorsalis, Zeugodacus cucurbitae, and Bactrocera latifrons, all responded significantly to 1-nonanol and analogues from rectal glands . A recent study showed that the olfactory functions of two clades of OR orthologs in three closely related species, Hylobius abietis, Dendroctonus ponderosae, and Ips typographus, are conserved, with ORs in one clade (HabiOR3, DponOR8, and ItypOR6) responding exclusively to 2-phenylethanol and those in the other clade (HabiOR4, DponOR9, and ItypOR5) responding to several green leaf volatiles . These results support the hypothesis that the functions of single-copy orthologous OR genes are relatively conserved during evolution and that these genes usually have similar functions and are involved in regulating important insect behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the responses of functionally conserved OSN classes are mediated via conserved odorant receptors (ORs) in closely related species. For example, several single-copy (1:1) OR orthologues have been identified in different species of the Curculionidae family ( Roberts et al, 2022 ). In that study, two sets of such OR orthologues were functionally characterized in three species, the bark beetles I. typographus and Dendroctonus ponderosae (Hopkins) as well as the pine weevil Hylobius abietis (L.) .…”
Section: Discussionmentioning
confidence: 99%
“…The OR gene family sequences identified from T. castaneum , Dendroctonus ponderosae , and Agrilus planipennis genomes were selected for participation in the construction of a phylogenetic tree to determine the branch positions of AglaORs , and ten functional Ors from M. Caryae , I. typographus , H. abietis , and R. ferrugineus were also included to determine whether they are homologous with AglaORs [ 18 , 22 , 23 , 31 , 32 ]. Maximum likelihood phylogenies were inferred using IQ-TREE [ 60 ] under a model automatically selected by IQ-TREE (‘Auto’ option in IQ-TREE) for 1000 ultrafast [ 61 , 62 ] bootstraps, as well as the Shimodaira–Hasegawa-like approximate likelihood-ratio test.…”
Section: Methodsmentioning
confidence: 99%
“…McarOR3 , McarOR5, and McarOR20 are sensitive to components of aggregation pheromones released by males, including (S)-2-methyl-1-butanol, 2-phenylethanol and (25,3R)-2,3-hexanediol, while ItypOR46 and ItypOR49 recognize the male aggregation pheromone components of I. typographus , including ipsenol and ipsdienol [ 26 , 30 ]. HabiOR3 , DponOR8, and ItypOR6 respond exclusively to 2-phenylethanol, and HabiOR4 , DponOR9, and ItypOR5 respond to angiosperm green leaf volatiles [ 31 ]. RferOR6 is narrowly tuned to alpha-pinene [ 32 ].…”
Section: Introductionmentioning
confidence: 99%